Characteristic Local Discontinuous Galerkin Methods for Incompressible Navier-Stokes Equations. (3rd May 2017) - Wang, Shuqin; Deng, Weihua; Yuan, Jinyun; Wu, Yujiang
Abstract: By combining the characteristic method and the local discontinuous Galerkin method with carefully constructing numerical fluxes, variational formulations are established for time-dependent incompressible Navier-Stokes equations inℝ 2 . The nonlinear stability is proved for the proposed symmetric variational formulation. Moreover, for general triangulations the priori estimates for the L 2 –norm of the errors in both velocity and pressure are derived. Some numerical experiments are performed to verify theoretical results.